2003
DOI: 10.1016/s1570-8705(03)00009-x
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation in sensor networks: an energy–accuracy trade-off

Abstract: -Wireless ad hoc sensor networks (WASNs) are in need of the study of useful applications that will help the researchers view them as distributed physically coupled systems, a collective that estimates the physical environment, and not just energylimited ad hoc networks. We develop this perspective using a large and interesting class of WASN applications called aggregation applications. In particular, we consider the challenging periodic aggregation problem where the WASN provides the user with periodic estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
146
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(147 citation statements)
references
References 14 publications
1
146
0
Order By: Relevance
“…Node s forwards a sequence of tuples to its parent P s during a round. It numbers these sequentially, e.g., (1,2,3,4,5,6). The highest sequence number is labeled n max = 6.…”
Section: Lazaridis Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Node s forwards a sequence of tuples to its parent P s during a round. It numbers these sequentially, e.g., (1,2,3,4,5,6). The highest sequence number is labeled n max = 6.…”
Section: Lazaridis Et Almentioning
confidence: 99%
“…If m = 0 (second case) then the message cannot be delivered, as there are no more retries left. Finally, for the third case: if the message is successfully forwarded by one hop, then it must clear k -1 hops with m retries; 4 otherwise it must clear all k hops with one less (m -1) number of retries. Now, consider the expected number of messages for m tries:…”
Section: Analysis Of Mechanisms For Fault-tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…A node at one specific time may be granted more access to the network than all other nodes if the program objective is still satisfied. For this reason, network resources are shared but it is not necessary that they may be equally distributed as long as the application performance is not degraded Since sensors are being densely deployed in WSNs, the detection of a the [4]. In this paper, we focus on constructing a data aggregation tree among any given set of source nodes.…”
Section: Iintroductionmentioning
confidence: 99%
“…The closest model to ours is described in [3]; however, in [3] the objective is to detect the occurrence of an event in an energy-efficient manner rather than to continuously collect the ambient conditions of the area. More recently, Boulis et al [1] and Kalpakis et al [6], considered the energy-accuracy trade off in sensor networks when the network is continuously monitored. Boulis et al, investigated the periodic aggregation and estimation problem when the observed data is time correlated.…”
Section: Introductionmentioning
confidence: 99%